2023
DOI: 10.1126/sciadv.adg0234
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative assembly of a designer peptide and silk fibroin into hybrid nanofiber gels for neural regeneration after spinal cord injury

Abstract: Local reconstruction of a permissive environment with biomaterials is a promising strategy to treat spinal cord injury (SCI). We reported a hybrid hydrogel fabricated from a small functional self-assembling peptide (F-SAP) and large silk fibroin (SF). The diffusion of SF micelles into F-SAP solution was driven by the dynamic synergy between osmotic pressure and F-SAP/SF electrostatic interactions, resulting in the rearrangement of SF micelles and the formation of rod-like filaments with axes nearly perpendicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Cartilage mainly plays a load-bearing and buffer role, while LKP hydrogels are not conducive to adhesion or mechanical properties in cartilage defects due to a lack of viscoelasticity, which limits their use. Based on the results of previous investigations, the conformation of SF can be transformed by hydrogen bonding and hydrophobic interactions when polypeptides or small molecules are incorporated into SF, and a stable hydrogel can be gradually formed within 5–30 min [ 22 , 23 ]. For practical application in cartilage defect repair, hydrogels that can be filled in situ immediately and solidified stably are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cartilage mainly plays a load-bearing and buffer role, while LKP hydrogels are not conducive to adhesion or mechanical properties in cartilage defects due to a lack of viscoelasticity, which limits their use. Based on the results of previous investigations, the conformation of SF can be transformed by hydrogen bonding and hydrophobic interactions when polypeptides or small molecules are incorporated into SF, and a stable hydrogel can be gradually formed within 5–30 min [ 22 , 23 ]. For practical application in cartilage defect repair, hydrogels that can be filled in situ immediately and solidified stably are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of glycidyl methacrylate (GMA) groups to SF by grafting increases the solubility of SF and can be used for photopolymerization to form hydrogels [ 20 , 21 ]. Moreover, some studies have confirmed that the addition of peptides can change the conformation of SF, creating composite hydrogels with variable mechanical properties [ 22 , 23 ]. However, peptide doping to change the SF conformation to form a stable hydrogel often takes 5–30 min, which is not favourable for clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…The study employed adult female Sprague Dawley (SD) rats weighing 200–250 g from the Experimental Animal Center of Southern Medical University. Complete cross-sections of spinal cord injury (SCI) were obtained according to established protocols [ 25 ]. Anesthesia was induced using a combination of 5 mg/kg xylazine and 70 mg/kg ketamine, and a 2–3 mm segment of T8-T10 spinal cord tissue was extracted.…”
Section: Methodsmentioning
confidence: 99%
“…The regeneration of nerves is highly dependent on the microenvironment of the injury site. By using bioinks to form an artificial extracellular matrix (ECM), it is possible to achieve local reconstruction of the target environment. Liu et al developed a novel biocompatible bioink consisting of functionalized chitosan, hyaluronic acid derivatives, and matrix gel (Figure aI). This bioink exhibited rapid gelation within 20 s and spontaneous covalent cross-linking ability, facilitating convenient one-step bioprinting of spinal cord-like constructs.…”
Section: Bioinks For 3d Bioprinting Of Tissues and Organsmentioning
confidence: 99%